Flaubert lecteur de Montaigne - Philippe Jousset (Flaubert: Revue Critique et Génétique)
Flaubert assiduously read Montaigne, who greatly contributed to his development. There are numerous parallels between the two writers, but beyond being a think tank, the former represented a source that the latter exploited according to his obsessions.  Such a use does not preclude misunderstandings and projections, so that Montaigne was adopted by Flaubert to reconstitute the myth of a kind of ingenuousness. Furthermore, Montaigne proves to be a prose model, particularly in the freer style of his Correspondence.